Pain and depression in women with rheumatoid arthritis: The effect of cognitive behavioral therapy - Mansouriyeh, Nastaran (Chronic Diseases Journal, 2020)
BACKGROUND: Pain is the main symptom of the disease in patients with rheumatoid arthritis (RA). This disease is the most common arthritis identified in women. Many studies have stated that there is a relationship between chronic pain and depression. The aim of this study was to examine the efficacy of the cognitive behavioral therapy (CBT) on reducing pain and depression in women with RA. METHODS: Four patients with RA were included in a single-subject study with multiple baseline design conducted in Tabriz, Iran, in 2017. Scores were measured with Beck Depression Inventory (BDI) and McGill Pain Questionnaire (MPQ) before and during treatment periods. RESULTS: The effect sizes according to the results of the BDI for the first, second, third, and fourth subject were 5.00, 0.66, 5.00, and 6.00, respectively. The effect sizes of the MPQ for the first, second, third, and fourth subject were 2.24, 3.44, 5.74, and 2.79, respectively. CONCLUSION: The symptoms of depression are high among patients with RA due to chronic pain. CBT significantly reduced pain and depression in patients with RA. CBT is a great help in reducing the physical and mental problems of patients with RA.